KGB Frontier-Guards in Lithuania After the War - Starkauskas, Juozas (Genocidas ir rezistencija, 1998)
In its attempts to crush our partisans, and the Lithuanian people in general, the border guards played a dual role: they blocked the border, thereby effectively preventing the Lithuanian resistance forces from receiving support from abroad, and at the same time, like the entire chekist army, they took part in battles against the partisans and in terror operations against the peaceful population. Compared to the chekist army, the border guards were remarkably fierce; our people called them ‘green–hat devils’.
Keywords: repressive structures; borderland; armed resistance